New Numerical Method for Solving Tenth Order Boundary Value Problems - Akgul, Ali; Akgul, Esra Karatas; Baleanu, Dumitru; İnç, Mustafa (Mdpi, 2018)
In this paper, we implement reproducing kernel Hilbert space method to tenth order boundary value problems. These problems are important for mathematicians. Different techniques were applied to get approximate solutions of such problems. We obtain some useful reproducing kernel functions to get approximate solutions. We obtain very efficient results by this method. We show our numerical results by tables.
Keywords: reproducing kernel Hilbert space method; tenth-order boundary value problems; reproducing kernel functions